Overcoming the challenges of designing optimized broadband vibroseis sweeps - Dean, Timothy; Quigley, J.; MacDonald, S.; Readman, C. (2014)
© 2014 SEG.Seismic vibrators are the preferred sources for land seismic surveys. Unfortunately, due to the mechanical and hydraulic constraints of the vibrator actuator, the typical swept bandwidth has been quite limited. The importance of broadband vibroseis data continues to grow in concert with other advances in seismic acquisition, processing and inversion. In this paper we show how improvements in the delivered source bandwidth can be made solely through careful vibrator sweep design. Given the influence of surface conditions on vibrator performance, such designs cannot be achieved using theoretical relationships or 'canned' drive functions. Instead, each survey requires a carefully designed, optimized and tested solution.